Asymmetric Responses to Earnings News: A Case for Ambiguity - Williams, Christopher D. (The Accounting Review, 2015)
ABSTRACT This study empirically examines the role of shocks to macro-uncertainty in shaping the responses of stock market participants to firm-specific earnings news. Specifically, I find that investors place greater weight on bad news following an increase in macro-uncertainty. By contrast, I find that investors place equal weight on both good and bad news following a decrease in macro-uncertainty. Furthermore, my findings show that these effects are more pronounced (1) for firms whose prior returns are more correlated with macro-uncertainty, (2) for firms that experience abnormally low trading volume during the earnings announcement, (3) for firms with relatively lower levels of institutional ownership, and (4) for firms with relatively higher information uncertainty. In sum, these findings provide novel empirical evidence that investors behave in a manner consistent with ambiguity aversion, with the effects strongest among unsophisticated investors.